2016
DOI: 10.1519/jsc.0000000000001055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical and Academic Stress on Illness and Injury in Division 1 College Football Players

Abstract: Stress-injury models of health suggest that athletes experience more physical injuries during times of high stress. The purpose of this study was to evaluate the effect of increased physical and academic stress on injury restrictions for athletes (n = 101) on a division I college football team. Weeks of the season were categorized into 3 levels: high physical stress (HPS) (i.e., preseason), high academic stress (HAS) (i.e., weeks with regularly scheduled examinations such as midterms, finals, and week before T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 5 publications
1
48
0
2
Order By: Relevance
“…Although prior research has identified decreased sleep as a consequence of overtraining and a possible risk factor for illness in athletes,12 we failed to identify a similar relationship. In addition, recent studies of collegiate football players46 and adolescent male soccer players24 found that illness risk was associated with increases in psychosocial stress. These prior studies have evaluated the effects of well-being over longer periods; however, it is possible that the increased risk of illness is due to cumulative effects over time which we did not evaluate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior research has identified decreased sleep as a consequence of overtraining and a possible risk factor for illness in athletes,12 we failed to identify a similar relationship. In addition, recent studies of collegiate football players46 and adolescent male soccer players24 found that illness risk was associated with increases in psychosocial stress. These prior studies have evaluated the effects of well-being over longer periods; however, it is possible that the increased risk of illness is due to cumulative effects over time which we did not evaluate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The development of physical fitness in youth is a complex process, which involves interaction of growth, maturation, and training (5, 15,16,145,219,261). Practitioners should appreciate the potential impact that other lifestyle factors will have on physical fitness development and physical activity engagement, including dietary behaviors (48,52), educational stress (159), sleep patterns (95,163), psychosocial health (24), and unrealistic external pressures from significant others such as parents or coaches (201,251). Cumulatively, all these factors can impact the engagement and enjoyment experienced by youth, adherence rates to training programs, and consequently the magnitude and rate of development of physical fitness.…”
Section: Long-term Athletic Development Pathways Shouldmentioning
confidence: 99%
“…Specifically, college football players were more likely to get injured during times of high academic stress. 18 Our findings may indicate that high school students either do not experience the same levels of stress as college students and/or their stress is unrelated to injuries. However, as this study only examined concussion related injuries, further exploration should be done at the high school level to examine the relationship between stress and all football related injuries.…”
Section: Discussionmentioning
confidence: 74%